Bam-Msimang, N.Y, The impact of government intervention on promoting small-scale commercial cannabis farmers in South Africa The impact of government intervention on promoting small-scale commercial cannabis farmers in South Africa - Bam-Msimang, Nomamiyandile (University of the Witwatersrand, Johannesburg, 2023)
This study explored the impact of government interventions aimed at promoting small- scale commercial cannabis farmers in South Africa. A semi-structured interview tool made up of thirteen open-ended questions was used to collect qualitative data from a study group of ten participants. The study group consisted of purposively sampled two policymakers and eight small-scale cannabis farmers. Participants’ responses were first recorded after obtaining their consent and afterwards transcribed. The qualitative data was inductively and thematically analysed to generate several main themes and sub-themes. These themes and sub-themes provided a deeper understanding and insights that highlighted the impact of government intervention on promoting small- scale commercial cannabis farmers in South Africa. The study findings revealed that despite the current government policies such as the Cannabis Master Plan and Phakisa Initiative aimed at deregulating commercial cannabis small-scale farmers still face considerable exclusion from this economic activity. To begin with, most small-scale farmers still face entry barriers that linked to legal, licence compliance and market competitiveness challenges. In addition, commercial cannabis farming has thus far failed to act as a driver for job creation and poverty alleviation in rural areas. This study found that the main cause of challenges faced by small-scale commercial farmers in this country has much to do the way government interventions are ineffectively implemented by various stakeholders. At most these interventions are marked by low levels of coordination, collaboration, and political will among officials tasked with implementing policies like the Cannabis Master Plan. Finally, the study made recommendations that can lead to increased effectiveness of government interventions and thus promote small-scale commercial cannabis farming in this country. Examples of these recommendations being conducting more awareness campaigns to sensitise law enforcers and rural cannabis small-scale farmers about commercial cannabis legislative frameworks, efforts to include rural farmers into formal cannabis supply chain and increase market competitiveness and accessibility thereof.
A research report submitted in partial fulfillment of the requirements for the degree of Master of Management to the Faculty of Commerce, Law, and Management, Wits Business School, University of the Witwatersrand, Johannesburg, 2024
Keywords: Cannabis Commercialisation; Cannabis Tourism; Decriminalisation; Landrace; Cannabis; Legalisation; South Africa’s Dagga Belt; UCTD; SDG-8: Decent work and economic growth